Analyzing the Challenges of Agricultural Crop Insurance among Microcredits: A Case Study of Sarjam Dehestan, Mashhad - Maryam Ghasemi; Lida Alizadeh (کاوش‌های جغرافیایی مناطق بیابانی, 2019)
The natural, social, economic and personal risks of agricultural production are inevitable, but those risks are manageable. To manage the risks of natural disasters and incidents, producers and economic policymakers in different societies use different strategies, such as insurance for agricultural products. However, farmers quite do not welcome agricultural insurances in the country. This study aims to identify the main challenges facing the development of agricultural insurance among microcredits. The research method is descriptive-analytic. With a review of exploratory and documentary studies, 23 challenges to the development of agricultural crop insurance were identified and ranked by 160 minor farmers based on the Likert scale. The identified factors were evaluated through the exploratory factor analysis by the SPSS software. There were seven main factors with 67% of variance explained. Accordingly, from the viewpoint of minor farmers, the main challenges facing the development of agricultural insurance include "The existence of an undesirable structure in the field of agricultural insurance" with 24.3%, "Farmers' dissatisfaction with the performance of the Agricultural Insurance Fund" with 12.1%, and "lack of space competition in the field of agricultural insurance" with 8.3% of variance. It is, therefore, recommended to make structural changes in the agricultural insurance sector by proper policy-making and government monitoring.